Technologies that enable congestion pricing : a primer. - United States. Federal Highway Administration. Office of Transportation Management (Washington, D.C. : U.S. Dept. of Transportation, Federal Highway Administration, 2008)
"This volume explores transportation technologies that enable congestion pricing. This document contains the following: the functional processes for tolling and congestion pricing; what technologies there are to consider; how the technologies are applied; examples of how technologies have been applied; what technologies may make it work better in the future"--p. 2.
Title from cover.
Performed by FHWA Office of Transportation Management
"October 2008"--Cover.
"FHWA-HOP-08-042"--Cover.
Includes bibliographical references (p. 23).
Also available on the Internet.
Keywords: Congestion pricing; Transportation -- Technological innovations; Transportation -- Finance